2002
DOI: 10.1111/j.1502-3885.2002.tb01063.x
|View full text |Cite
|
Sign up to set email alerts
|

Regressions and transgressions of the Baltic basin reflected by a new high‐resolution deglacial and postglacial lithostratigraphy for Arkona Basin sediments (western Baltic Sea)

Abstract: 2002 (June): Regressions and transgression s of the Baltic basin re ected by a new high-resolutio n deglacia l and postglacia l lithostratigraphy for Arkona Basin sediments (western Baltic Sea). Boreas, Vol. 31, pp. 151-162. Oslo. ISSN 0300-9483.Seismoacoustic pro les from the Arkona Basin show a late Pleistocene and Holocene successio n of several distinct re ectors. The physical , sedimentological , mineralogical and geochemica l propertie s of more than 30 sediment cores were analysed in order to assign the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
3
14
0
Order By: Relevance
“…and, despite possible re-deposition, could be interpreted as coastal sediments deposited after the final regression of the Baltic Ice Lake (Moros et al 2002). This date is consistent with other similar dates determined in this area (Lampe 2005) and with the assumption that the water level during the early Preboreal Chronozone was at 25 m b.s.l.…”
Section: Baltic Ice Lake Stagesupporting
confidence: 90%
See 4 more Smart Citations
“…and, despite possible re-deposition, could be interpreted as coastal sediments deposited after the final regression of the Baltic Ice Lake (Moros et al 2002). This date is consistent with other similar dates determined in this area (Lampe 2005) and with the assumption that the water level during the early Preboreal Chronozone was at 25 m b.s.l.…”
Section: Baltic Ice Lake Stagesupporting
confidence: 90%
“…The above-described composition reflected the dominance of mineral deposition with an input of organic detritus presumably due to re-deposition from flooded land areas and transported during the Ancylus regression into deeper parts of the basin. Similar sediments of terrestrial origin of organic material deposited with coarse mineral material were also identified previously in the Arkona Basin (Moros et al 2002) and the Bornholm Basin .…”
Section: Ancylus Lake Stagesupporting
confidence: 82%
See 3 more Smart Citations